2014
DOI: 10.1007/978-3-319-08795-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Two Procedures for Analyzing the Reliability of Open Government Data

Abstract: Abstract. Open Government Data often contain information that, in more or less detail, regard private citizens. For this reason, before publishing them, public authorities manipulate data to remove any sensitive information while trying to preserve their reliability. This paper addresses the lack of tools aimed at measuring the reliability of these data. We present two procedures for the assessment of the Open Government Data reliability, one based on a comparison between open and closed data, and the other ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Table 3 summarizes the results over the entire dataset. 5 Our simulation reduces the distance (i.e. the error) with respect to the projection, as confirmed by a Wilcoxon signed-rank test [35] at 95% significance level.…”
Section: 1]) the Model Issupporting
confidence: 58%
See 1 more Smart Citation
“…Table 3 summarizes the results over the entire dataset. 5 Our simulation reduces the distance (i.e. the error) with respect to the projection, as confirmed by a Wilcoxon signed-rank test [35] at 95% significance level.…”
Section: 1]) the Model Issupporting
confidence: 58%
“…time intervals, by means of the Poisson process [15]), and more sophisticated to improve the uncertainty management part (e.g., Mixture Models [27], Nested [29] and Hierarchical Dirichlet processes [30] and Markov Chain Monte Carlo algorithms [13,25]). Secondly, we will work on the generalization of the data analysis procedures, by combining this work with a previous work on the analysis of the reliability of open data [5] and extending both of them.…”
Section: Automating Piracy Attacks Analysismentioning
confidence: 99%
“…Novais et al (2013) provided a literature review of open government data studies from 2007 to 2012, in which they indicated the need to broaden the geographic coverage of open government data research and to improve the quality criteria for assessing open government data, including to ensure the trustworthiness of data (Ceolin et al , 2014; Léveillé and Timms, 2015). Novais et al (2013) suggested that the term open government data began to appear in 2007, following the publication of the original eight open data principles, which stated that open data should be complete, primary not aggregated, timely, accessible, machine-processable, non-discriminatory, non-proprietary and license-free (https://public.resource.org/8_principles.html).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Government Data (GD) is another precious resource whose potential is yet to be explored for suitability studies, especially in developing countries. OGD, as a form of authoritative data, is regarded as of higher quality data than VGI [7,8]. Various open government data contain points of interest (POI), which offer a useful reflection of the spatial distribution, spatial pattern, and categories of infrastructures, which are an important source of suitability indicators.…”
Section: Introductionmentioning
confidence: 99%